Disease Mapping for Surveillance and Control at House Level Using Geoinformation Freeware - Chansang, Chitti; Nakhapakorn, Kanchana; Chansang, Uruyakorn; Sawanpanyalert, Prathom (Journal of Health Science of Thailand, 2018)
Disease mapping at the house level for surveillance and control is an important tool for the epidemiology and disease control. However, it is quite complicated for drawing maps with precision that correctly depicting the real space. In some cases, the map can be drawn by hand sketch in field study such as ground survey mapping for epidemiological assessment. Nowadays, progress has been made for using Geoinformation for mapping. However, in some situations there are limits on the budget and workers with Geoinformation skills in the field of public health. Therefore, in this study, the appropriate Geoinformation freeware and procedures for disease mapping in public health were studied. Epidemiological and entomological data for DHF at village 10 in Hua Samrong subdistrict, Plaeng Yao district, Chachoengsao province, were used as a case study for the disease mapping. The results recommended using selected freewares : Google Earth, DNR Garmin and MapWindowGIS with the details for mapping procedure in each program. The websites for down loading the freeware were shown. The resulting maps showed the locations of survey houses with satellite imagery, houses with cases and groups of houses within 100-meter radius, and houses with and without Aedes larvae. Person interested in disease mapping, could follow the mapping procedures. The disease mapping can be applied to research and as disease control measures such as an early warning system, exchange of information, and defining target for control plans.